Kajian Persentase Tutupan Karang Dengan Metode Manta Tow Di Perairan Pulau Matan Kabupaten Raja Ampat - Dwi Indah Widya Yanti; Sefli Ryno; Melisa Masengi; Handayani (INTEGRATED OF FISHERIES SCIENCE, 2022)
The waters of Matan Island are one of the waters found in Raja Ampat Regency, this water area has very diverse water resources, one of which is coral reef ecosystems. This study aims to determine the percentage of coral reef cover and coral reef conditions using the Manta Tow method. During the observations, it was found that the percentage of coral reef cover along 10 observation points with an average coral cover percentage of 29%, for dead corals with a cover percentage of 16%, coral fractures 23%, 19% sand and other biota 13%. Conditions along the observation trajectory are dominated by coral reefs and coral fractures. The distribution of coral fractures on Matan Island was caused by explosives used by local fishermen which caused damage to coral reefs.